The emergence of patent races in lignocellulosic biofuels, 2002–2015. (September 2017) - Toivanen, Hannes; Novotny, Michael
Abstract: How does increasing economic and technological interest in biofuels shape the nature of the intellectual property rights (IPR) in the industry? Is the technological nature of biofuel patents and inventions, as well as the business itself undergoing a transformation? This article provides a patent analysis of lignocellulosic biofuels with U.S. patent publications between 2002 and 2015 in order to shed light on the broader economic and regulatory factors affecting the development of new technologies in the area. Patent applications in the technology have increased about eightfold in this period and count about 130–150 per year currently, and could soon reach 200 annual filings. Specifically, we analyse in what ways the nature of lignocellulosic biofuel technologies is changing, and our results suggest that this business is indeed being transformed by increasing research and development (R&D) and IPR efforts, material in an evident patent race. We document a relatively small, but nascent technology, with some key technology areas increasing between four- and tenfold, over the last decade. Technologically leading countries are the U.S., followed by Germany, Japan, France and the U.K. We argue that intensified global and industry-wide claims for IPR reveal an ongoing patent race with multiple implications for the industry and engineering community. Most importantly, industry's technological interdependence is likely to increase as the likelihood for broad, exclusive patent regimes diminishes, making the industry more likely to explore increasingly collaborative technological solutions when carrying out R&D and investing in new production facilities in the future. Highlights: Lignocellulosic biofuels is small but strongly emerging technology. Expected rate of new US patent applications is 150-200 per year. Intense patent races characterize the lignocellulosic biofuels technology currently. The nature of patents is changing and collaborative R&D will increase. Chemical and oil firms are patent most actively in the technology.